Unbiased Proteomic Profiling Strategy for Discovery of Bacterial Effector Proteins Reveals that Salmonella Protein PheA Is a Host Cell Cycle Regulator - Na, Ha-Na; Yoo, Young-Hwa; Yoon, Chang No; Lee, Jun-Seok (CELL PRESS, 2015)
Salmonella utilizes a type III secretion system to inject bacterial effector proteins into the host cell cytosol. Once in the cytosol, these effectors hijack various biochemical pathways to regulate virulence. Despite the importance of effector proteins, especially for understanding host-pathogen interactions, a potentially large number of effectors are yet to be identified. Here, we demonstrate that unbiased chemical proteomic profiling using off-the-shelf fluorescent probes leads to the discovery of a host cell cycle regulator encoded in the Salmonella genome. Our profiling combined with bioinformatic analysis implicates 29 Salmonella as potential effectors. We follow up on the top candidate, chorismate mutase-P/prehenate dehydratase, PheA, and present evidence that PheA is an effector that mimics E2F7 transcription factor of the host cell and promotes G1/S cell cycle arrest. This validates our strategy and opens opportunities for effector identification in the future.
Keywords: III SECRETION SYSTEM; E2F7; MECHANISM; BINDING; CANCER; PROBES